The existential trilemma of EMU in a model of fiscal target zone. (10th March 2022) - Della Posta, Pompeo; Tamborini, Roberto
Abstract: Objectives: Is the Economic and Monetary Union (EMU) truly 'irreversible' as stated in the treaties? (i) From the sovereign debt crises of the 2010s, and the outbreak of the COVID-19 pandemic, we draw the lesson that when exposed to large, systemic shocks the EMU faces a trilemma among preserving its irreversibility, monetary orthodoxy and fiscal orthodoxy: irreversibility can only be saved by relaxing one of the twin orthodoxies or both. (ii) We show how central monetary/fiscal backstops to irreversibility can be designed in a consistent manner that minimises their amplitude and mitigates the moral hazard concerns. Methods: We present a novel fiscal target zone model of the EMU, where public debt is hit by stochastic shocks and member governments under monetary and fiscal orthodoxy are willing to abide by their commitment to debt stability only up to an upper bound of their feasible fiscal effort. Shocks large enough push the stabilisation fiscal effort beyond the feasibility constraint, in which case a government would opt for default on debt service and breakup of EMU membership—similarly to the abandonment of an exchange-rate agreement. Results: For the EMU to be truly irreversible, ramparts for extraordinary times are necessary beside regulations for ordinary times. The alternative to these devices is reformulating the treaties with explicit and regulated exit procedures.